A Bibliometric and Quantitative Review of Renewable Energy–Powered Mine Dewatering Systems: Trends, Performance, and Gaps - Miftahul Fadillah; Erkata Yandri (Heca Sentra Analitika, 2026)
Renewable energy integration into mine dewatering systems has gained increasing attention amid rising energy costs, decarbonization pressures, and hydrological variability in mining operations. However, existing studies remain fragmented across hydrogeological modeling, hybrid energy optimization, and environmental assessment, limiting cross-study comparability and system-level integration. This study conducts a structured bibliometric and quantitative synthesis to examine the evolution of research, collaboration patterns, thematic concentration, and methodological gaps in renewable energy–based mine dewatering systems between 2015 and 2025. A PRISMA-based dataset of 43 eligible publications was analyzed using co-authorship networks, keyword co-occurrence mapping, temporal overlay visualization, and composite bibliometric scoring. The results reveal a transition from hydrogeology-focused research toward hybrid renewable integration and energy storage–oriented systems. Publication activity increases significantly after 2020, with a peak in citation impact around that time. Energy storage, renewable integration, and groundwater management emerge as dominant research hotspots, while system-level optimization, stochastic hydrological modeling, real-time control, and long-term validation remain underdeveloped. Quantitative evidence indicates energy savings of approximately 12–25% and carbon emission reductions of 20–40%, although these remain constrained by heterogeneous baselines and deterministic modeling approaches. This study proposes a conceptual analytical framework integrating bibliometric structural analysis, temporal performance evaluation, and gap-driven synthesis to support uncertainty-aware and system-level evaluation of renewable-based mine dewatering systems. The findings guide scalable, integrated dewatering strategies across diverse mining contexts.